Religious Violence in Indonesian Muslim Society - Jajat Burhanudin (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2006)
Acts of violence in the name of religion have frequently in lndonesia in recent times, a country in zuhich most of its inhabitants are Muslim. Acts of violence are usually a result of efforts, for example, to eradicate sinful acts in society, wipe out shirk (idolatry), and defend God's name. Yet, this phenomenon of violence is indeed aery complex. It appears in a number of forms and involves a large variety of factors.DOI: 10.15408/sdi.v13i2.573